[PP.10.18] REDUCTION IN BLOOD PRESSURE AND CARDIAC HYPERTROPHY IN RESISTANT HYPERTENSIVE SUBJECTS: A FIVE-YEAR FOLLOW-UP STUDY. (September 2016) - Brunelli, V.; Cruz, L.A.; Faria, A.P.C.; Correa, N.B.; Sabbatini, A.R.; Barbaro, N.R.; Modolo, R.G.P.; Ritter, A.M.V.; Moreno, H.
Abstract : Objective: Resistant hypertension (RH) is defined as the condition whose the blood pressure (BP) remains above the target (above140/90mmHg) despite the concurrent use of three or more classes of antihypertensive (anti-HT) at optimal doses. It is known that cardiovascular risk increases with the lack of BP control. Thus, optimized treatment - pharmacological or no pharmacological - is important to attempt the reduction of the risk of cardiovascular events in subjects with RH. Design and method: In this study, we performed a retrospective cohort with 57 RH patients regularly followed-up in a specialized clinic during a five years period, from 2009 until 2014, in order to compare clinical and biochemical data. We assessed office and ambulatory (ABPM) BP measurements. The left ventricular hypertrophy (LVH) was assessed by echocardiography. The biochemical tests such as aldosterone, renin, glucose, glycated hemoglobin (HbA1c), total cholesterol, high-density lipoprotein cholesterol (HDL); low-density lipoprotein cholesterol (LDL), very-low-density lipoprotein cholesterol (VLDL) and triglycerides. Microalbuminuria and urinary sodium excretion were also evaluated. Results: The office BP levels decreased from 2009 to 2014 (135/78 mmHg vs. 122/72mmHg, p < 0.01) as well as ABPM (147/85mmHg vs. 136/78 mmHg, p = 0.02). The number of anti-HT drugs used increased in 2014, due to the greater use proportion of beta-blockers (BBs) and mineralocorticoid receptor antagonist (MRA). In addition, the hypoglycemic agents and statins use increased in the same period. Even with the increase of the number of drugs over the evaluated period, we found that the defined diary dose of the medications in 2014 were similar when compared to 2009. Finally, LVH significantly decreased in 2014 compared to 2009 (93 ± 27 g/m2 vs. 143 ± 38 g/m2, p < 0.0001, respectively). Conclusions: We conclude that an intensive treatment may improve BP control and target organ damage. A close follow-up is essential to assess and assist the evolution of the patients, and consequently, provide better cardiovascular outcomes.